Pengembangan Sistem Informasi Pelayanan Desa Berbasis Web Dengan Metode Prototyping Pada Desa Leran - Agung Kurniawan; Muhammad Chabibi; Renny Sari Dewi (STMIK Budi Darma, 2020)
Current web-based administrative services are not only for government at the city or regional level, but now the village also needs it to support its government activities. According to Law No. 6 of 2014 the village is a legal community unit that has the territorial boundaries that are authorized to regulate and administer government affairs, the interests of the local community based on community initiatives, original rights, and / or traditional rights that are recognized and respected in the Republic of the Republic of Republic's government system. Indonesia. In the current technological era, there are many services for villages that use and utilize information technology so that the service process becomes easier, more transparent and faster. For this reason, in this study we had the opportunity to develop a web-based Village Service Information System in Leran village, in developing the system this time we used a prototyping method. This system will have several features, including: making independent reports, submitting a letter of introduction from the village and online, making a biodata of the village community, and also containing the profile of the village of Leran. The results of this research are a village service information system that can help the work of government officials in the village of Leran, and also facilitate the villagers in obtaining information about services or other information in the village of Leran.